2021
DOI: 10.3389/fcvm.2021.795016
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Three-Dimensional Right Ventricular Ejection Fraction in Patients With Asymptomatic Aortic Stenosis

Abstract: Background: The right ventricular (RV) function is an important prognostic marker of asymptomatic aortic stenosis (AS). However, previous publications have not addressed the additive value of conventional RV parameters over left heart parameters. Whether three-dimensional echocardiography (3DE)-derived RV ejection fraction (RVEF) has prognostic utility independent of 3DE derived left heart parameters is also unknown. We investigated the prognostic utility of 3DE RVEF in patients with asymptomatic AS.Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…When we included 15 echocardiography parameters, CART selected 3D RVEF first, followed by LV diastolic function parameter (mitral E/e') and LV systolic function parameter (3D LVESVI). The results suggest that among echocardiographic parameters, 3D RVEF is more important than LV diastolic and systolic parameters to predict future outcome, which agreed with the previous study in patients with asymptomatic aortic stenosis (24).…”
Section: Current Studysupporting
confidence: 91%
“…When we included 15 echocardiography parameters, CART selected 3D RVEF first, followed by LV diastolic function parameter (mitral E/e') and LV systolic function parameter (3D LVESVI). The results suggest that among echocardiographic parameters, 3D RVEF is more important than LV diastolic and systolic parameters to predict future outcome, which agreed with the previous study in patients with asymptomatic aortic stenosis (24).…”
Section: Current Studysupporting
confidence: 91%
“…RVEF might be a universal biomarker that refines risk stratification. 10 12,14,16-23 independent studies were included in the final quantitative analysis (Figure 1), which reported the impact of unit change of RVEF and TAPSE (n = 8), 12,15,17,[19][20][21][22][23] or FAC (n = 7), 12,[18][19][20][21][22][23] or FWLS (n = 7) 16,[18][19][20][21][22][23] on clinical outcomes (allcause mortality and/or cardiopulmonary adverse events) as HRs. Four studies were prospective, while 6 were retrospective.…”
Section: Highlightsmentioning
confidence: 99%
“…The mean (6SD) age of the patient population was 63 6 15 years, 46% were female, and the follow-up duration ranged from 3 to 44 months. Three studies included patients with pulmonary hypertension exclusively, 14,16,20 1 included patients with COVID-19 only, 23 1 included patients with dilated cardiomyopathy only, 22 1 included patients with aortic stenosis only, 18 1 included heart failure patients with preserved left ventricular (LV) ejection fraction (HFpEF) only, 19 and the remaining 3 studies included populations with a mixture of cardiovascular diseases. 12,17,21 Outcomes Table 1 contains the definitions of end points assessed in each included study.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…In three instances (including 3-3 studies), there was an apparent overlap between the patient cohorts; 9,13-17 therefore, studies with a higher number of participants were included. 13,15,17 Overall, ten 13,15,[17][18][19][20][21][22][23][24] independent studies were included in the final quantitative analysis (Figure 1), which reported the impact of unit change of RVEF and TAPSE (n=8), 13,16,18,[20][21][22][23][24] or FAC (n=7), 13,[19][20][21][22][23][24] or FWLS (n=7), 17,[19][20][21][22][23][24] on clinical outcomes (all-cause mortality and/or cardiopulmonary adverse events) as HRs. Four studies were prospective, while six were retrospective.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The mean (±SD) age of the patient population was 63±15 years, 46% were females, and the follow-up duration ranged from 3 to 44 months. Three studies included patients with pulmonary hypertension exclusively, 15,17,21 one included patients with COVID-19 only, 24 one included patients with dilated cardiomyopathy only, 23 one included patients with aortic stenosis only, 19 one included heart failure patients with preserved left ventricular (LV) EF (HFpEF) only, 20 and the remaining three studies included populations with a mixture of cardiovascular diseases. 13,18,22 Outcomes Table 1 contains the definitions of endpoints assessed in each included study.…”
Section: Patient Characteristicsmentioning
confidence: 99%